The Impact of Voice Assistants on Consumer Intention to Use Self-Driving Cars - Bilro, R.G. (Academy of Marketing Conference - AM2023, 2023)
This study examines the influence of voice assistants’ attributes on consumer intention to use self-driving cars and WOM intentions. Results indicate that a positive attitude toward voice assistant attributes positively impacts the intention to use self-driving cars. The study suggests that integrating voice assistants in self-driving cars can increase consumer adoption.